Adsorption of bisphenol a and dibutyl phthalate in graphene oxide: an Ab Inito study - Oliveira, Patrícia Viera de; Silva, Ivana Zanella da; Fagan, Solange Binotto (Disciplinarum Scientia | Naturais e Tecnológicas, 2019)
Endocrine disruptors encompass a wide class of substances that cause adverse effects to organisms or their progeny. In this work, we emphasize bisphenol A and dibutyl phthalate, both constituents of plastics, which are widely used in modern life. These compounds were detected in effluent treatment plants, and new technologies were required for the treatment of these substances. Adsorption is a promising technique for the treatment of effluents due to its low cost and efficiency. Highlighting here the graphene oxide, a material used as nano adsorbent due to its high surface area, stands out for this application. In this work, we evaluated the interaction of graphene oxide and the endocrine disruptors’ bisphenol A and dibutyl phthalate via computer simulation, analyzing the electronic and structural characteristics of the systems isolated and adsorbed. The results show that the interactions occur in the physical adsorption regime, with the adsorption energy of approximately 1 eV for the most stable configurations, promising for the application of this system as a filter to absorb the pollutants.